2020
DOI: 10.1515/teme-2020-0055
|View full text |Cite
|
Sign up to set email alerts
|

Temperature monitoring in the subsurface during single lip deep hole drilling

Abstract: The surface quality and the subsurface properties such as hardness, residual stresses and grain size of a drill hole are dependent on the cutting parameters of the single lip deep hole drilling process and therefore on the thermo-mechanical as-is state in the cutting zone and in the contact zone between the guide pads and the drill hole surface. In this contribution, the main objectives are the in-process measurement of the thermal as-is state in the subsurface of a drilling hole by means of thermocouples as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The experimental setup is shown schematically in Figure 1a. This setup is part of a more complex experimental framework, which is not part of the present study [10,14,15]. The experimental investigations were performed on the deep hole drilling machine Mö-TM-HF-16-2-S (Walter Möck GmbH, Sonnenbühl, Germany).…”
Section: Sld Experimentsmentioning
confidence: 99%
“…The experimental setup is shown schematically in Figure 1a. This setup is part of a more complex experimental framework, which is not part of the present study [10,14,15]. The experimental investigations were performed on the deep hole drilling machine Mö-TM-HF-16-2-S (Walter Möck GmbH, Sonnenbühl, Germany).…”
Section: Sld Experimentsmentioning
confidence: 99%
“…They stated that the surface roughness increased at the hole exit under all experimental conditions. Wegert et al [8] examined the temperature and wear in the drilling zone. They stated that with a drill bit, the temperature value increased to 150 0 C after three dry drilling operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Suitable cutting parameters to produce process-favorable short-breaking chips [24] and the precise control of the cooling lubricant [25,26] therefore play an important role to prevent insufficient bore hole quality and excessive tool wear [23,27,28]. In studies by Wegert et al [29], a lack of cooling lubricant supply led to chipping of the cutting edges of single-lip deep hole drills. However, Wegert et al [29] observed an influence of the cooling lubricant supply on the temperature development in the subsurface zone of the bore hole wall.…”
Section: Introductionmentioning
confidence: 99%
“…In studies by Wegert et al [29], a lack of cooling lubricant supply led to chipping of the cutting edges of single-lip deep hole drills. However, Wegert et al [29] observed an influence of the cooling lubricant supply on the temperature development in the subsurface zone of the bore hole wall. The temperature of the subsurface zone, which is influenced by the cooling lubricant supply, is also the focus of Schmidt's current investigations.…”
Section: Introductionmentioning
confidence: 99%